(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article is devoted to the study of the linguistic features of French-Uzbek translations in the field of tourism. The article considers the interaction of language and culture, semantic and syntactic aspects, as well as terminology issues that arise in the process of translation from French into Uzbek. The article analyzes tourist terms and expressions in French, their equivalents in Uzbek, and translation methods. The importance of cultural context in the translation process, as well as factors determining the role of the translator, are discussed. The article also contributes to a deeper understanding of the linguistic connections between French and Uzbek and provides recommendations aimed at improving the quality of translations in the field of tourism.